2009
DOI: 10.3166/rmpd.10.609-624
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Design for Curved Road Sections Fatigue Performance of Interfaces and Longitudinal Top-down Cracking in Multilayered Pavements

Abstract: This paper focuses on damage processes other than the main one observed and studied in pavement design. Previous research has targeted the experimental fatigue performance of tack coats. The French Pavement Design method has been chosen herein to illustrate how interface fatigue performance can lead to improved design, especially when pavements are subjected to repeated horizontal loadings. In a curved pavement section, longitudinal top-down cracking is observed, and this damage process may also be taken into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…As far as the testing temperature is concerned, the FG interface at 10 • C provides higher shear fatigue performance compared to those at 20 • C for the same reinforcement (Figure 16). This is in accordance with previous investigations carried out with various shear tests in cyclic modality on unreinforced specimens [34,39,61] and in static modality on reinforced specimens [45], where an improvement of interlayer resistance was measured at low temperatures. Therefore, it can be assumed that as the temperature decreases, since the asphalt concrete is a thermo-dependent material, the interlayer becomes stiffer and more loading cycles of the same stress intensity are needed to cause the failure of the specimen.…”
Section: Interlayer Shear Fatigue Curvesupporting
confidence: 93%
See 1 more Smart Citation
“…As far as the testing temperature is concerned, the FG interface at 10 • C provides higher shear fatigue performance compared to those at 20 • C for the same reinforcement (Figure 16). This is in accordance with previous investigations carried out with various shear tests in cyclic modality on unreinforced specimens [34,39,61] and in static modality on reinforced specimens [45], where an improvement of interlayer resistance was measured at low temperatures. Therefore, it can be assumed that as the temperature decreases, since the asphalt concrete is a thermo-dependent material, the interlayer becomes stiffer and more loading cycles of the same stress intensity are needed to cause the failure of the specimen.…”
Section: Interlayer Shear Fatigue Curvesupporting
confidence: 93%
“…Nevertheless, road pavements are subjected to cyclic traffic loads with magnitudes considerably lower than those that cause the interface failure during static shear tests. In this sense, static (i.e., monotonic) shear tests can be used for quality assessment of the interlayer bonding properties at failure, whereas the adoption of cyclic shear tests can offer a more complex evaluation of interlayer bonding [34][35][36][37]. Moreover, cyclic shear test results can be used for modeling or pavement design purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The interface fatigue model is expressed on the basis of the model currently used to determine the lifetime of asphalt concrete mixtures. A recently published paper has focused on use of the interface fatigue model to improve the design of curved road sections [20]. Table captions Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The works of Yoo [ 8 ] have shown that vertical shear strain at the edge of the tire is more critical than extensional strain. Petit [ 9 ] has shown that the TDC fatigue of a pavement structure is initiated by superficial extension strains that are induced by tangential stresses applied to the surface of the roadway. A crack initiation model was developed by Lytton [ 10 ].…”
Section: Introductionmentioning
confidence: 99%